Cabaran sosial dalam pelaksanaan zakat kalangan masyarakat Muslim Bangkok - Waemrene Waepa; Shofian Ahmad; Mohd Nasran Mohamad; Muhamad Razak Idris (Penerbit Universiti Kebangsaan Malaysia, 2018)
Nowadays, there are three major institutions which are officially responsible for managing the zakat affairs of the Muslim community in Bangkok, namely the Bangkok Islamic Religious Council, Bangkok Islamic Center Foundation and Santichon Bangkok Foundation. These three institutions face social challenges which are part of the obstacles towards the enhancement of the role of zakat among the Muslim society in Bangkok. Those social challenges can be divided into three aspects, namely the understanding, attitude and appreciation of the Muslim society towards zakat obligations. The study is based on interviews with Muslim leaders in Thailand namely Arron Boochom, the President of Bangkok Islamic Religious Council; Ismail Ali, an Adviser to the Islamic Centre of Bangkok; Banson bin Kasan, a Committee Member of Santichon Islamic Foundation; Samad Matlulim, the President of the Central Foundation Bangkok; Prasert Wongsan, the Deputy President of Santichon Islamic Foundation and Issra Santhisath, a lecturer at Chulalongkorn University. Based on the findings, these social challenges must be continously addressed by all parties in the Muslim society to ensure that the management of zakat in Bangkok will generate positive benefits enhancing the prosperity of sosio-economic life of Muslim society in Bangkok. Some recommendations are suggested in order to overcome the social challenges, namely the promotion of zakat forums, implemention of a population census and the establishment of zakat law in Thailand.